2005
DOI: 10.1143/jjap.44.732
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Gas-Phase H-Atom Number Density by Tungsten Phosphate Glass

Abstract: A numerical calculation method for the optical trapping force which is appropriate for single lensed fibre trapping (SLFT) is proposed. The piconewton optical trapping forces on a yeast cell in SLFT as a function of the position along two horizontal orthogonal axes are measured experimentally by static and dynamic methods, respectively. The order of magnitude and the characteristics of the theoretical trapping force curve calculated by our method are the same as those of the experimental measurement curve. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The absolute densities were evaluated under two conditions. In one case, W was used as a catalyst and the temperature was 2060 K. The NH 3 when a Ru-coated wire was used and the temperature and the pressure were 1660 K and 120 Pa, respectively.…”
Section: Detection Of Nh Radicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absolute densities were evaluated under two conditions. In one case, W was used as a catalyst and the temperature was 2060 K. The NH 3 when a Ru-coated wire was used and the temperature and the pressure were 1660 K and 120 Pa, respectively.…”
Section: Detection Of Nh Radicalsmentioning
confidence: 99%
“…Recently, Yasui and coworkers have shown that GaN films can be grown from NH 3 and trimethylgallium by employing a hot-mesh chemical vapor deposition method [1,2]. They used W and Ru-coated W meshes and found that the crystallinity of GaN films grown using the Ru-coated W mesh was better than that grown using the W mesh at low catalyst temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental apparatus and the procedure were similar to those described elsewhere. 6,[28][29][30] The H-atom density measurements were carried out by using two types of vacuum chambers made of stainless steel. One type was a cylindrical one with an internal diameter of 90 mm and a height of 350 mm, which is schematically illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…6,[28][29][30] The output of a dye laser ͑Lumonics, HD-500͒ pumped with a Nd:YAG laser ͑Spectra Physics, PRO-190͒ at 729.6 nm was doubled in frequency by a ␤-BaB 2 O 4 crystal and then tripled by a mixture of Kr and Ar to produce Lyman-␣ light. The typical pressures of Kr and Ar were 13 and 40 kPa, respectively, while the pulse energy of the laser at the doubled stage ͑364.8 nm͒ was 10 mJ.…”
Section: Methodsmentioning
confidence: 99%